Conservative Surgical Management of Mesh Erosion Following Abdominal Sacrocolpopexy - Rani, Shikha (J Midlife Health, 2020)
Abdominal sacrocolpopexy (ASC) provides global support to the prolapsed vault. Hence, it is one of the successful procedures done along with pelvic organ prolapse to prevent future vault prolapse. Mostly, the synthetic mesh is used for the ASC. As, it provides a better strength. However, synthetic meshes are associated with more complications as compared to the autologous graft. Mesh erosion is one of the furious complication with the synthetic meshes. Commonly, these eroded meshes become infected, thus requiring removal. Due to the formation of adhesion and fibrosis around the mesh even the removal of these meshes is difficult. In our institute, we have performed 50 adbominal sacrocolpopexy over the past 9 years. Four mesh erosions had occurred. Two meshes were infected, which responded well to the antibiotics and conservative surgical removal of the mesh.